PEMBENTUKAN PORTOFOLIO OPTIMAL PADA INDEKS KOMPAS 100 PERIODE 2013-2014 - Hamdani, Ardi Sanjaya; Murhadi, Werner Ria; Sutejo, Bertha Silvia (University of Surabaya, 2015)
This study aims to establish the optimal portfolio of Kompas 100 index. Optimal portfolio is a portfolio consisting of stocks that can generate the maximum return value to the same risks or generate the same return value with the most minimal risk. This study is a quantitative approach. This study uses the company listed in Indonesia Stock Exchange. Optimal portfolio in this study formed from stocks that are continuously enrolled in the Kompas 100 index in the period August 2009 to July 2014. Optimal portfolio is formed by using a single index model. Then the performance calculation is done using the Sharpe, Treynor, and Jensen ratio. The results of this study showed that from the 100 stocks which include in the Kompas 100 index, only 19 stocks that can form the optimal portfolio. Portfolio return value is 51.10% with the risk portfolio value is 15.47%. Based on the Sharpe ratio, Treynor and Jensen, the optimal portfolio formed by 5.271% value for Sharpe, 3.958% value for Treynor and 1.588% value for Jensen ratio. So, based on that ratio, optimal portfolio has already had a good performance and the stocks included in the portfolio can be said to be eligible to be purchased by investors.